Protective ileostomy creation after anterior resection of the rectum: Shared decision‐making or still subjective?. (28th December 2022) - Balla, Andrea; Saraceno, Federica; Rullo, Marika; Morales‐Conde, Salvador; Targarona Soler, Eduardo M.; Di Saverio, Salomone; Guerrieri, Mario; Lepiane, Pasquale; Di Lorenzo, Nicola; Adamina, Michel; Alarcón, Isaias; Arezzo, Alberto; et al.
Abstract: Aim: The choice of whether to perform protective ileostomy (PI) after anterior resection (AR) is mainly guided by risk factors (RFs) responsible for the development of anastomotic leakage (AL). However, clear guidelines about PI creation are still lacking in the literature and this is often decided according to the surgeon's preferences, experiences or feelings. This qualitative study aims to investigate, by an open‐ended question survey, the individual surgeon's decision‐making process regarding PI creation after elective AR. Method: Fifty four colorectal surgeons took part in an electronic survey to answer the questions and describe what usually led their decision to perform PI. A content analysis was used to code the answers. To classify answers, five dichotomous categories (In favour/Against PI, Listed/Unlisted RFs, Typical/Atypical, Emotions/Non‐emotions, Personal experience/No personal experience) have been developed. Results: Overall, 76% of surgeons were in favour of PI creation and 88% considered listed RFs in the question of whether to perform PI. Atypical answers were reported in 10% of cases. Emotions and personal experience influenced surgeons' decision‐making process in 22% and 49% of cases, respectively. The most frequently considered RFs were the distance of the anastomosis from the anal verge (96%), neoadjuvant chemoradiotherapy (88%), a positive intraoperative leak test (65%), blood loss (37%) and immunosuppression therapy (35%). Conclusion: The indications to perform PI following rectal cancer surgery lack standardization and evidence‐based guidelines are required to inform practice. Until then, expert opinion can be helpful to assist the decision‐making process in patients who have undergone AR for adenocarcinoma.